Gamification on EFL Learner with Deaf Disability: A Systematic Literature Review - Iim Nurhasanah; Nafan Tarihoran; Purnama Rika Perdana (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
This study aims to examine the effectiveness of gamification-based technology in English language learning for students with Special Education Needs (SEN), particularly those with hearing impairments or deaf disabilities. A systematic literature review (SLR) was conducted using the PRISMA framework, which includes three main stages: identification, screening, and inclusion. A total of 183 articles were retrieved from Google Scholar, Scopus, and Web of Science, using keywords related to gamification, EFL learning, and deaf disabilities from publications between 2020 and 2024. After filtering for relevance and methodological rigor, 10 studies were selected for analysis. The findings indicate that gamification enhances engagement, motivation, and learning outcomes for students with hearing impairments by integrating interactive storytelling, visual cues, sign language-based content, and adaptive feedback mechanisms. Several studies highlight the positive impact of mobile gamification applications, digital storytelling, and reward-based learning on vocabulary acquisition, reading comprehension, and speaking skills. Moreover, gamification fosters self-directed learning and provides real-time feedback, allowing students to learn at their own pace. Despite its benefits, challenges such as limited access to high-quality gamified platforms, the need for teacher training, and concerns about excessive screen time remain. However, with ongoing advancements in educational technology, gamification has significant potential to be further optimized for inclusive education. Future research should explore long-term impacts and the integration of emerging technologies such as virtual and augmented reality in gamified EFL learning for students with hearing impairments.